Организация и оптимизация компьютерного моделирования дифракционных процессов методом дискретных особенностей - Мищенко, Виктор Олегович; Паточкин, Борис Викторович (НТУ "ХПИ", 2015)
При всестороннем исследовании антенн, ретрансляторов и других подобных устройств существует потребность в расчетах параметров дифракции электромагнитных волн на металлических экранах для многих вариантов формы и волновых чисел. Время компьютерного моделирования критично. Перспективными в такой ситуации становятся вычислительные методы дискретных особенностей, в частности, метод дискретных токов (МДТ). В статье разработан метод организации компьютерного моделирования по МДТ с пользованием особенностей архитектуры персональных компьютеров и даны результаты проверки эффективности этого метода.

In the comprehensive study of antennas and repeaters there is a need in the calculation of the parameters of diffraction of electromagnetic waves on metal screens for many forms and values of wave numbers. The time of computer modeling is critical. Using computational methods of discrete singularities, in particular the discrete currents method (DCM), becomes promising in this situation. Current reserves of improving them by using sequential algorithms are exhausted. These algorithms need to be parallelized to exploit the architectural features of modern PCs. The authors have developed a library of software components, which takes into account the important architectural features of modern PCs and allows to increase the speed of computation in several or even dozens of times. The paper shows the architecture of modeling systems for the calculations by the modified DCM, the method of preparation of primary information, the method of testing the speed efficiency and the results of such testing.
Organization and optimization of computer simulation of diffraction processes by discrete singularities method
Keywords: волны электромагнитные; число волновое; модель математическая; архитектура компьютера; тайлинг; регистр векторный; OpenMP; electromagnetic wave; wave number; computer model; architecture; tiling; vector registers